Analisis Sistem Manajemen Keselamatan dan Kesehatan Kerja (K3) Pada Kantor Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Batang Hari - Ratna Ratna; Nadiatul Khoiroh; Muhammad April Riansyah (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2020)
The purpose of this study was to determine the occupational health safety management system at the Office of the Regional Disaster Management Agency (BPBD) in Batang Hari Regency. The research method used is descriptive qualitative. Methods of data collection by library research and field research from interviews and observations. Methods of data analysis by data reduction, data presentation, and data inference. The results showed that from 3 dimensions related to perceptions of safety management within the organization, namely (1) commitment to management leadership where leaders prioritize work safety for members, (2) empowerment of safety management, leaders give confidence to all members (BPBD) because leaders are confident in their abilities. (3) management fairness towards work safety, management treats all members equally, there is no difference between new and old members and 4 dimensions related to perceptions of the work group, among others (1) workers' commitment to the promotion of work safety, indicating commitment to work safety, being active in the promotion of work safety and caring about the safety of others (2) showing that BPBD members prioritize community safety without neglecting their own safety (3) learning, communication and trust, in the workplace in discussing i su-safety issues, learn from work experience, help each other to be able to work safely, accept input related to work safety properly and believe in each other's ability to ensure safety while working is good (4) trust in the effectiveness of work safety systems However, workers' perceptions regarding the belief in the effectiveness of the work safety system run by members of the Batang Hari BPBD have been going well.